2018
DOI: 10.1523/jneurosci.0789-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Play an Active Role in Obesity-Associated Cognitive Decline

Abstract: Obesity affects >600 million people worldwide, a staggering number that appears to be on the rise. One of the lesser known consequences of obesity is its deleterious effects on cognition, which have been well documented across many cognitive domains and age groups. To investigate the cellular mechanisms that underlie obesity-associated cognitive decline, we used diet-induced obesity in male mice and found memory impairments along with reductions in dendritic spines, sites of excitatory synapses, increases in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
161
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 171 publications
(178 citation statements)
references
References 79 publications
16
161
0
1
Order By: Relevance
“…Notably, the detrimental effects of microglial ablation on motor learning are linked to a reduction in synapse formation in the motor cortex in the learning phases of this task . Likewise, the detrimental effects of high‐fat diet on novel object recognition performance can be restored by preventing excessive microglia‐mediated pruning of dendritic spines . These data again suggest that both the absence of microglia and their excessive activity can encourage excess synaptic pruning with a negative outcome for cognition.…”
Section: The Role Of Microglia In Cognitionmentioning
confidence: 99%
See 4 more Smart Citations
“…Notably, the detrimental effects of microglial ablation on motor learning are linked to a reduction in synapse formation in the motor cortex in the learning phases of this task . Likewise, the detrimental effects of high‐fat diet on novel object recognition performance can be restored by preventing excessive microglia‐mediated pruning of dendritic spines . These data again suggest that both the absence of microglia and their excessive activity can encourage excess synaptic pruning with a negative outcome for cognition.…”
Section: The Role Of Microglia In Cognitionmentioning
confidence: 99%
“…There is some evidence to suggest microglial activation is detrimental to cognition and that removing microglia altogether may be beneficial. Cope et al have recently shown that 10 weeks of high‐fat diet in the mouse leads to microglial activation in the hippocampus, as well as cognitive deficits, and preventing this activation with knockdown of the fractalkine receptor or with minocycline restores cognition. Although microglial activation outside of the hypothalamus is rarely seen with short‐term high‐fat feeding, there is evidence to suggest that it can occur with longer exposures and that this may be linked with cognitive dysfunction .…”
Section: The Role Of Microglia In Cognitionmentioning
confidence: 99%
See 3 more Smart Citations